VALIDASI MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK PENINGKATAN KARAKTER NASIONALISME PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Yuyun Puji Utami Ning Muntiani; Novialita Angga Wiratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop and validate an animated video learning medium for Pancasila Education to enhance nationalism charactr. The study addresses the challenge of uninnovativ and unengaging learning media in Pancasila Education, which hinders students' interest and active participation in fostering nationalism. Utilizing a Rsarch and Development (R&D) approach with the ADDIE model, this study specifically focuses on the